MicroRNA biogenesis and cytoophidia in Drosophila melanogaster - Mohd Azzam, M (2012)
This thesis contains two separate projects. The first project involves the study of Argonaute 1 (Ago1) which is a member of the Argonaute/PIWI protein family involved in small RNA-mediated gene regulation. In Drosophila, Ago1 plays a specific role in microRNA (miRNA) function. Previous studies have demonstrated that Ago1 regulates the fate of germline stem cells. However, the function of Ago1 in other aspects of oogenesis is still elusive. Here, the function of Ago1 was analysed in the female germline and follicle cells. The Ago1 protein is enriched in the oocyte and also highly expressed in the cytoplasm of follicle cells. Clonal analysis of multiple ago1 mutant alleles shows that mutant egg chambers often contain only eight nurse cells and lack an oocyte which is phenocopied in dicer-1, pasha and drosha mutants. This implies a general role of miRNAs in this process. Further analysis of the clones shows that Ago1, Dicer-1, Drosha and miR-124a play a role in maintaining follicle cell integrity. Additionally, it was found that Ago1 protein levels were lowered when miRNAs were not present and that overexpression of miR-124a increased the steady state level of Ago1 proteins. These were believed to be the effect of Ago1 protein stability. In the meantime, a second project was carried studying a novel filamentous structure called cytoophidia which contains CTP synthase (CTPS) was analysed. Previous studies have shown that the cytoophidia is prominent in the egg chambers but how and why CTPS forms cytoophidia is still unclear. Here, the different CTPS isoforms were analysed and only CTPS isoform C was found to form cytoophidia. This isoform could also induce cytoophidia formation in other tissues that does not have obvious cytoophidia formation. Then, it was identified that the first 56 amino acid of CTPS isoform C is the important region for cytoophidia formation. Furthermore, ctps mutants were generated and analysed. CTPS mutations caused lethality during the larval stage and when maternal contribution was removed, lethality was seen during embryogenesis.